Development of Magnetic Digital Comics in Science Learning to Improve Student Learning Outcomes in Elementary Schools - Lanto Mohamad Kamil Amali; Nova Elysia Ntobuo; Ritin Uloli; Yasin Mohamad; Muhammad Yunus (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop digital comics for learning magnetism in learning Science in Elementary Schools. This type of research is development research, which refers to the Four-D. The location of this research is at Kota Tengah 80 Public Elementary School, Bulangu Timur 1 Public Elementary School, and Telaga Biru 1 Public Elementary School. The results of the study show that digital comic magnets developed for science learning in elementary schools: (1) are categorized as valid and feasible; (2) Practically used, this is indicated by the very good response from students with a percentage of 90% in the limited trial class and 93.75% in the extended trial class. The implementation of learning in the limited trial class obtained an average percentage of 90.91%, while in the extended trial class it was 96.15%; (3) Effectiveness, indicated by good student activity with a percentage of 82% in both limited trial classes and extended trial classes, as well as student learning outcomes that are in very good criteria. Based on this, the digital comics magnet that has been developed is stated to be valid, practical and effective, so that it can be used in the science learning process in class V of elementary school